Satisfaction with transport and enjoyment of the commute by commuting mode in inner Sydney. (10th December 2015) - Rissel, Chris; Crane, Melanie; Wen, Li Ming; Greaves, Stephen; Standen, Chris
Abstract : Issue addressed: Travel satisfaction has become an increasingly popular construct for the assessment and monitoring of transport systems and services. However, satisfaction may not adequately assess emotion or mood towards walking and cycling, especially when infrastructure is biased towards motor vehicle modes. In this exploratory study we sought to examine the associations of both satisfaction with transport and enjoyment from the commute to work or study by commute mode in an Australian inner city context where transport mode choices are readily available. Methods: As part of the Sydney Transport and Health Study, 675 baseline study participants (2013) were invited to complete an online questionnaire in September/October 2014 and 512 did so (76% response rate). Participants who did not travel to work were removed from analyses, giving complete data for 473. Participants provided data on usual travel mode to work or study, satisfaction with transport, enjoyment from their commute, and demographics and neighbourhood factors. Results: The main mode of travel to work or study in this inner city sample was public transport (41%), followed by motor vehicle (27%), walking (21%) and cycling (10%). Most participants were satisfied with their transport (82%), with little variation by mode. Walkers (49%) and cyclists (52%) reported far higher levels of enjoyment from their commute than car drivers (14%) or public transport users (10%), with an adjusted odds ratio of 6.18 (95% confidence interval 3.10–12.29, P < 0.001) for walking and an adjusted odds ratio of 6.15 (95% confidence interval 2.68–14.08, P < 0.001) for cycling. Conclusions: People who walked or cycled to work or study in inner Sydney reported higher levels of enjoyment from their commute compared with those who drove. This suggests enjoyment may be another benefit of active travel. So what?: Focusing on 'enjoyment' associated with walking or cycling to work may be a positive motivator to encourage active travel. Abstract : Being satisfied with your transport, and enjoying the way you travel, are very different concepts and vary considerably by transport mode. This study compared satisfaction with transport and enjoyment of the commute by commute mode in inner Sydney, Australia, where transport mode choices are readily available. People who walked or cycled to work or study reported higher levels of enjoyment from their commute compared with those who drove, highlighting a benefit of active travel.